Italian national consensus statement on management and pharmacological treatment of phenylketonuria - Alberto Burlina; Giacomo Biasucci; Maria Teresa Carbone; Chiara Cazzorla; Sabrina Paci; Francesca Pochiero; Marco Spada; Albina Tummolo; Juri Zuvadelli; Vincenzo Leuzzi (Orphanet Journal of Rare Diseases, 2021)
Abstract Background Phenylketonuria (PKU) is a rare inherited metabolic disorder caused by defects in the phenylalanine-hydroxylase gene (PAH), the enzyme catalyzing the conversion of phenylalanine to tyrosine. PAH impairment causes phenylalanine accumulation in the blood and brain, with a broad spectrum of pathophysiological and neurological consequences for patients. Prevalence of disease varies, with peaks in some regions and countries, including Italy. A recent expert survey described the real-life of clinical practice for PKU in Italy, revealing inhomogeneities in disease management, particularly concerning approach to pharmacotherapy with sapropterin hydrochloride, analogous of the natural PAH co-factor, allowing disease control in a subset of patients. Therefore, the purpose of this paper is to continue the work initiated with the expert survey paper, to provide national guidances aiming to harmonize and optimize patient care at a national level. Participants The Consensus Group, convened by 10 Steering Committee members, consisted of a multidisciplinary crowd of 46 experts in the management of PKU in Italy. Consensus process The Steering Committee met in a series of virtual meeting in order to discuss on clinical focuses to be developed and analyzed in guidance statements, on the basis of expert practice based evidence, large systematic literature review previously performed in the expert survey paper, and evidence based consensus published. Statements were re-discussed and refined during consensus conferences in the widest audience of experts, and finally submitted to the whole consensus group for a modified-Delphi voting. Results Seventy three statements, divided in two main clinical areas, PKU management and Pharmacotherapy, achieved large consensus in a multidisciplinary group of expert in different aspects of disease. Importantly, these statements involve guidances for the use of sapropterin dihydrochloride, still not sufficiently implemented in Italy, and a set of good practice to approach the use of novel enzyme replacement treatment pegvaliase. Conclusions This evidence-based consensus provides a minimum set of guidances for disease management to be implemented in all PKU centers. Moreover, these guidances represent the first statement for sapropterin dihydrochloride use, implementation and standardization in Italy, and a guide for approaching pegvaliase treatment at a national level on a consistent basis.